Supplementary figures and tables from Genetic rescue in an inbred Arctic fox ( Vulpes lagopus ) population - Malin Hasselgren; Anders Angerbjörn; Nina E. Eide; Rasmus Erlandsson; Øystein Flagstad; Arild Landa; Johan Wallén; Karin Norén (2018)
Caption for each figure and table can be found in the document